Measuring the research performance of LIS academicians in Pakistan using Google Scholar, Scopus and Web of Science databases - Midrar Ullah (IJoLIS, 2023)
Purpose: This study ascertains and compares the quantity of publications, citations, h-indices, rankings and the most cited papers of Pakistani LIS academicians in Google Scholar (GS), Scopus and World of Science (WOS) databases. Design/methodology/approach: The publications of 32 LIS faculty members were scrutinized. Searches by academicians’ name were performed in GS, Scopus and WOS in March 2021.